“Paleontologia da perversão” : o caminho proposto por Barbara Cassin para recuperar o pensamento sofístico em face da destruição efetuada pela hegemonia platônico-aristotélica - Fraga, David dos Santos (2021)
This dissertation aims to analyze and reconstitute Sophistic thought as it emerges from the research of the French scholar, Barbara Cassin. The dominant philosophical tradition has delegated Sophistic thought to the status of pseudo, Not-Being, false. Conversely, Sophistic thought understands philosophy as a fact of language. This can be seen in Gorgias, who makes an inversion of Parmenides' poem that compromises the “Being” of ontology by showing the Not-Being of Being, and in Antiphon, who makes the transition from the physical to the political. Meanwhile, Philostratus and Lucian later reappeared with the Second Sophistic, being no longer part of the philosophers but of the speakers who inaugurate the novel, a discourse that is known as pseudo and claims to be pseudo, renouncing all ontological adequacy to produce its own world-effect.